2012
DOI: 10.1186/1748-717x-7-217
|View full text |Cite
|
Sign up to set email alerts
|

Factors of influence on acute skin toxicity of breast cancer patients treated with standard three-dimensional conformal radiotherapy (3D-CRT) after breast conserving surgery (BCS)

Abstract: Purpose/ObjectivesStandard 3D-CRT after BCS may cause skin toxicity with a wide range of intensity including acute effects like erythema or late effects. In order to reduce these side effects it is mandatory to identify potential factors of influence in breast cancer patients undergoing standard three-dimensional conformal radiation therapy (3D-CRT) of the breast and modern systemic therapy.Materials/MethodsBetween 2006 and 2010 a total of 211 breast cancer patients (median age 52,4 years, range 24–77) after B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
1
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 29 publications
5
48
1
4
Order By: Relevance
“…Previous reports have suggested that patients with a larger breast size may have a more severe skin reaction than those with a smaller breast size. 10,23 The data revealed that the consistency between the 2 methods in the axillary and breast areas tended to be limited to patients with a large breast size. This finding implies that the TPS may be a feasible, alternative method for predicting skin reactions in this type of vulnerable patient.…”
Section: Discussionmentioning
confidence: 95%
“…Previous reports have suggested that patients with a larger breast size may have a more severe skin reaction than those with a smaller breast size. 10,23 The data revealed that the consistency between the 2 methods in the axillary and breast areas tended to be limited to patients with a large breast size. This finding implies that the TPS may be a feasible, alternative method for predicting skin reactions in this type of vulnerable patient.…”
Section: Discussionmentioning
confidence: 95%
“…Increased risk of acute dermatitis was found with standard fractionation schedules, 3D-CRT technique compared to IMRT, largest breast size, high BMI, and smoking. 10,[15][16][17] Across these studies there was significant disagreement on the most significant factors for the development of acute breast radiation dermatitis, likely due to the smaller study number of these retrospective reviews. In our study, BMI, total radiation dose, and radiation fractionation schedule appear to be the most important factors for development of breast radiation dermatitis.…”
Section: Discussionmentioning
confidence: 98%
“…Radiation pneumonitis and pulmonary fibrosis are important complications of radiation‐induced pneumonitis for breast cancer 21, 22, 23. Occurrence rate of complications is significantly correlated with irradiation volume and dose in lung tissues.…”
Section: Discussionmentioning
confidence: 99%